Analisis Strategi Manajemen ZISWAF dalam Meningkatkan Kesejahteraan Ekonomi Umat: Studi pada ZISWAF Center Politeknik Negeri Medan - Ayu Niatasya Nasution; Supaino Supaino; Muhammad Zuhirsyan; Rikwan Effendi S Manik; Rahmadani Rahmadani; Suherman Suherman (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to analyze the ZISWAF management strategies implemented by the ZISWAF Center of Politeknik Negeri Medan in improving the economic welfare of the Muslim community, particularly among the academic community classified as mustahik. Additionally, the study identifies challenges and obstacles in managing ZISWAF funds and explores solutions applied to address those challenges. The research adopts a qualitative approach with a descriptive method. Data were collected through in-depth interviews with seven relevant informants. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. SWOT analysis using IFAS and EFAS matrices was conducted to formulate appropriate strategies. The findings reveal that management functions—planning, organizing, actuating, and controlling—have been effectively applied. The WO (Weaknesses–Opportunities) strategy was identified as the most suitable approach, emphasizing the improvement of internal weaknesses by optimizing external opportunities. This study is expected to serve as a reference for sustainable and adaptive ZISWAF management development.